Ethnic differences in lipid and lipoprotein metabolism in pregnant women of African and Caucasian origin. - Koukkou, E (1994)
AIMS--To investigate differences in serum lipid, lipoprotein and apolipoprotein concentrations in pregnant women of different ethnic origin. METHODS--Serum lipid, lipoprotein and apolipoprotein concentrations were measured in 232 women (114 Caucasians, 118 Africans/Afro-Caribbeans), who presented consecutively for screening for gestational diabetes in the third trimester of pregnancy. RESULTS--African/Afro-Caribbean pregnant women had lower serum concentrations of total cholesterol, low density lipoprotein cholesterol, triglycerides, and apolipoprotein B and higher high density lipoprotein cholesterol and Lp(a) lipoprotein concentrations compared with Caucasian women. Apolipoprotein A1 concentrations were similar in the two groups. The differences were not attributable to differences in weight, age, parity, or postload plasma glucose levels. CONCLUSION--Ethnic origin is an important determinant of serum lipid, lipoprotein and apolipoprotein concentrations during pregnancy.